Mean Sojourn and Mean Return Time of the Buy-hoard-sell Strategy of Bitcoin Exchange Prices - Mba, Ifeoma Christy; Mba, Emmanuel Ikechukwu; Ogbuabor, Jonathan Emenike; Arazu, Winnie Ogochukwu (International Journal of Economics and Financial Issues, 2018)
A three state Markov chain procedure for testing the Bitcoin exchange rate prices via the mean return and mean sojourn times were applied in this study from January 2016 to February 2017. The data were of a daily basis. The analysis were conducted on the Buy-Hoard-Sell strategies of the Bitcoin exchange rate and it was discovered that the hoard state was a more difficult one to enter and once entered, it takes a longer time to come out. It was also discovered that the buy state and sell states were preferred because it has a high speed of transition. The steady state values also showed that in the long run, it takes 49% for the buy state to achieve its steady state level, 43% for the sell state and 8% for the hoard state. With these information, the hoard state was still not preferred in the Bitcoin exchange market. Keywords: Markov, Buy-Hoard-Sell, Bitcoin JEL Classifications: C10, G15